A clinical trial of two parenteral nutrition solutions in neonates. Issue 7 (July 1990) - McIntosh, N; Mitchell, V
Abstract : Sixty eight neonates requiring total or supplemental parenteral nutrition in the first week of life were randomly allocated either Vamin 9 glucose (n = 34) or MB233G (n = 34) in a double blind trial. Twenty infants were withdrawn: four because they died before 5 days of age and 16 because the amino acids were required for less than the five days of the trial. The solutions were isocaloric (1.6 MJ/l, 380 kcal/l) and with the same nitrogen content (2.79 g/l) and were infused at rates and volumes determined by clinical staff on the basis on the infants, clinical condition and serum electrolyte biochemistry. There was an excess of deaths in the group treated with Vamin 9 glucose particularly related to babies weighing greater than or equal to 1000 g. Infants less than 1000 g receiving the Vamin 9 glucose preparation required amino acids for twice as long. There was no significant difference between the weight losses or head circumference during the study period. Plasma aminograms in the group receiving Vamin 9 glucose showed concentrations of phenylalanine, tyrosine, proline, serine, and aspartic acid to be significantly higher than the reference range. Multiple regression analysis suggested that phenylalanine was the primary abnormality. The intravenous amino acid preparation MB233G maintained the plasma aminogram of newborn infants within the reference range of normal newborn infants.